Các yếu tố tác động đến sự phát triển của mô hình trường học xanh: nghiên cứu tại một số trường trung học cơ sở ở thành phố Hồ Chí Minh - Hồ, Thị Thu Hiền; Lê, Hồ Hạnh Dung; Nguyễn, Hồ Thanh Ngân (Tạp chí Giáo dục, 2025)
In the context of an escalating global environmental crisis, the Green School model plays a vital role in promoting education for sustainable development. However, the implementation and improvement of Green Schools model at schools still face numerous challenges. This study identifies key factors influencing the development of Green School initiatives in lower secondary schools in Ho Chi Minh City. These factors include the quality of the learning environment, financial resources, school infrastructure, community engagement, and energy optimization. Identifying these core components holds theoretical significance in the field of education for sustainable development and offers practical implications for educational administrators in building strategies and effectively applying the Green School model in accordance with local conditions.